ASPM May be Related to the Malignant Progression of Hepatitis B and is Associated With a Poor Prognosis of Hepatocellular Carcinoma - Tan, Siyou; Chen, Wenyan; Kong, Gaoyin; Wei, Lai (Frontiers in Bioinformatics, 2022)
Background: Hepatitis B virus (HBV) is a causative agent of hepatocellular carcinoma (HCC). Until now, the mechanism behind the progress of hepatitis B fibrosis to HCC remains largely unknown. This study aims to examine the candidate biomarkers and pathways involved in HBV-associated HCC. Methods: Gene expression profiles were retrieved from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified using the GEO2R tool after which functional enrichment analysis, protein-protein interaction (PPI) analysis, genetic alteration analysis, prognostic analysis, immune infiltration analysis, co-expression genes prediction, and miRNA-gene network construction were performed. Results: 22 hub genes were identified, which were all highly expressed in HCC, and overexpression of these genes was all associated with significantly worse survival in HCC patients. More significantly, ASPM also showed increased expression levels in non-tumor tissues with advanced liver fibrosis. With the progression of liver fibrosis and the closer tumor center of HCC, the higher expression of ASPM was identified. ASPM was considered to be the most promising biomarker because it also showed the highest genetic alteration frequency among the hub genes. Also, the infiltration levels of B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells were all positively correlated with the expression of ASPM. Conclusion: These findings may help in the development of strategies and candidate drugs for the treatment of HBV-related HCC and improve the effectiveness of personalized treatment in the future. ASPM was upregulated in both hepatitis B cirrhosis and HCC and could be a potential predicting biomarker.